2019
DOI: 10.1371/journal.pone.0208141
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning models to predict disease progression among veterans with hepatitis C virus

Abstract: BackgroundMachine learning (ML) algorithms provide effective ways to build prediction models using longitudinal information given their capacity to incorporate numerous predictor variables without compromising the accuracy of the risk prediction. Clinical risk prediction models in chronic hepatitis C virus (CHC) can be challenging due to non-linear nature of disease progression. We developed and compared two ML algorithms to predict cirrhosis development in a large CHC-infected cohort using longitudinal data.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 20 publications
0
43
0
Order By: Relevance
“…Additional studies have used machine learning to focus on the challenge of predicting progression in HCV patients. Konerman et al analysed approximately 11,000 HCV patients to identify those at risk of developing cirrhosis using the national Veterans Health Administration data 20 . They found that boosting survival tree-based models outperformed other methods with an area under the receiver operator characteristic curve of 0.77.…”
mentioning
confidence: 99%
“…Additional studies have used machine learning to focus on the challenge of predicting progression in HCV patients. Konerman et al analysed approximately 11,000 HCV patients to identify those at risk of developing cirrhosis using the national Veterans Health Administration data 20 . They found that boosting survival tree-based models outperformed other methods with an area under the receiver operator characteristic curve of 0.77.…”
mentioning
confidence: 99%
“…Moreover, ML approaches have shown recently their power in disease prognosis with applications in e.g. hepatitis prediction [45], classification of diabetic patients [46,47] and lung cancer screening [48]. They have also recently enabled to give brain specific interactions probability of each gene with all the genes of the network and their probability association with ASD [49] but without differentiating NT and ASD babies.…”
Section: Discussionmentioning
confidence: 99%
“…It can detect complex underlying patterns of features to predict the binary target variable of belonging to the ASD group. This algorithm gives state-of-the-art results in a wide range of classification applications, especially in healthcare and diagnosis of diseases [45,46,72,73].…”
Section: Classification Processmentioning
confidence: 99%
“…In a follow-up study utilizing a cohort of 72,683 veterans with CHC, boosted survival tree-based models using longitudinal data consistently outperformed prediction of development of cirrhosis in CHC patients at 1, 3, and 5 years as opposed to standard cross-sectional statistical methods. (51) PSC ML methods have been investigated in patients with PSC both preceding and following transplantation. In an effort to be able to better identify patients with PSC at risk for HD, Eaton et al examined a large cohort of 509 PSC patients to derive an algorithm predictive of HD (ascites, variceal hemorrhage, and encephalopathy) using the GBM algorithm.…”
Section: Viral Hepatitismentioning
confidence: 99%